Short Communication: Characteristics of the endangered Javan banteng (Bos javanicus) spermatozoa - Vincentia Trisna Yoelinda; Raden Iis Arifiantini; Dedy Duryadi Solihin; Muhammad Agil; Dedi Rahmat Setiadi; Yohana Tri Hastuti; Jansen Manansang; Dondin Sajuthi (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Yoelinda VT, Arifiantini RI, Solihin DD, Agil M, Setiadi DR, Hastuti YT, Manansang J, Sajuthi D. 2023. Short Communication: Characteristics of the endangered Javan banteng (Bos javanicus) spermatozoa. Biodiversitas 24: 759-766. Morphology and morphometry of spermatozoa become essential fertility parameters in domestic and wild animals. Such morphological abnormalities can arise from genetic or environmental origins and cause fertility deprivation. Semen collection using transrectal massage has been used in several domestic and wild animals and is known to be simpler, safer, and less painful than artificial vaginas and electro-ejaculation. This study aimed to evaluate morphological and morphometrical features of the banteng spermatozoa head. The objective of this study was also, to evaluate the use of transrectal massage as a semen collection protocol. This study was conducted in Taman Safari Indonesia, Cisarua, Bogor, West Java, involving one banteng (Bos javanicus) bull. Semen samples were collected weekly, smeared, and stained with a modified Williams' staining method. This study found ten types of head morphological abnormality, comprising several major defects, with several types known to be the genetic origin. There were also nine types of spermatozoa tail abnormalities and teratoid form abnormalities. The total normal spermatozoa proportion in this study was 54.30±1.74%. Morphometric dimensions of length, width, and area head of banteng spermatozoa were 9.88±0.01 µm, 4.91 µm, and 38.12±0.05 µm2, respectively, with a tail length of 60.48±0.03 ?m. Although our result was limited by the number of samples available for the study, this first report on the banteng bull's sperm morphology and morphometry still need to be considered. The possibility of transrectal massage use for banteng semen collection protocol demonstrated in this study may be helpful to support the conservation approach in terms of breeding program strategy.